Penerapan E-Commerce Bagi UMKM Sebagai Pemasaran Digital dalam Menghadapi Revolusi Industri 4.0 - Ketut Sumardana; Sussanti Sussanti; Veronica Krini Damayanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The digital industrial revolution 4.0 has had a significant impact on various sectors in Indonesia, including the business sector. Currently, one of the digital marketing strategies that UMKM can adopt to promote their products and develop their businesses is the use of e-commerce. This scientific article was written to reveal the importance of digital marketing in facing the challenges of the digital industrial era 4.0, especially for UMKM. The method used in writing this article is qualitative descriptive research, with data collection through literature study. Data collection was carried out by referring to books, journals and online sources, which were then cited as the theoretical basis for writing. The research results show that digital marketing is a relevant strategy to be implemented in the current digital era, especially for UMKM. By implementing digital marketing, UMKM have a great opportunity to develop their business and expand their market reach. E-commerce as a form of digital marketing needs to be implemented by UMKM because it makes it easier to market their products.